Effects of dietary cysteamine in quails on performance, hatchability, plasma biochemical and sex hormone levels - Kanbur, Gülşah; Parlat, Sinan Sefa (Journal of the Hellenic Veterinary Medical Society, 2022)
This study was designed to determine the effects of a single dose of dietary Cysteamine (Cys) on growth and laying performance, meat properties, hatchability, and plasma glucose, cholesterol, and sex hormone levels of quail in two experiments that followed each other. Trial 1 (T1): A total of two hundred, 1-d old quail (Coturnix coturnix japonica) chicks were randomly allocated to 1 of two treatment groups with 5 replicates, either a control group (basal diet) or a treatment group that contain 90 mg Cys per kg basal diet. During the 5 weeks growth period performance data regarding the growth period were collected. At the end of T1, a total of 30 quail were slaughtered, and color values, pH, and meat macronutrients were determined of breast meat. Data from T1 showed that the inclusion of 90 mg Cys in the diet did affect neither growth performance nor breast meat parameters of quail. Trial 2 (T2): At the end of T1, 40 from each treatment and a total of 80, six-weeks-old quail were selected randomly to use in the laying period experiment. Feeding with Cys added (90 mg/kg basal diet) and control (Basal) diets have been lasted in two treatment groups for 10 weeks for laying period. Laying and hatching performance data collected during T2, at the end of the trial, a total of 20 quails were sacrificed and plasma glucose, cholesterol, and sex hormone levels detected. Results of T2 displayed that 90 mg /kg feed dietary Cys increased egg mass (P< 0.05), however, it was ineffective on other laying and hatching performance parameters. Whereas plasma glucose level was not altered, plasma cholesterol level significantly decreased with the presence of Cys in the diet (P< 0.05). Moreover, dietary Cys significantly increased plasma sex hormones levels in both sexes. Concluded, 90 mg dietary Cys did not show an improving or depressing effect on the growth, laying, or hatching performance of quails however, its cholesterol-lowering impact and boosting effects on plasma sex hormones are noteworthy.